Internationalization of education of the study program in french language the Sales management from the point of view of the relation student - institution - Kita, Jaroslav
Dimenzie spolupráce vo sfére frankofónneho vzdelávania na Ekonomickej univerzite. Rozvoj študijného programu Sales management.